Harmonious Biomaterials for Development of In situ Approaches for Locoregional Delivery of Anti-cancer Drugs: Current Trends - Singh, Amrinder; Thakur, Shubham; Sharma, Tushit; Kaur, Manjot; Sahajpal, Nikhil S.; Aurora, Rohan; Jain, Subheet Kumar (Current Medicinal Chemistry, 2020)
Locoregional drug delivery is a novel approach for the effective delivery of anti-cancer agents as it exposes the tumors to high concentration of drugs. In situ gelling systems have fetched paramount attention in the field of localized cancer chemotherapy due to their targeted delivery, ease of preparation, prolonged or sustained drug release and improved patient compliance. Numerous polymers have been investigated for their properties like swelling along with biodegradation, drug release and physicochemical properties for successful targeting of the drugs at the site of implantation. The polymers such as chitosan, Hyaluronic Acid (HA), poloxamer, Poly Glycolic Lactic Acid (PGLA) and Poly Lactic Acid (PLA) tend to form in situ hydrogels and have been exploited to develop localized delivery vehicles. These formulations are administered in the solution form and on exposure to physiological environment such as temperature, pH or ionic composition they undergo phase conversion into a hydrogel drug depot. The use of in situ gelling approach has provided prospects to increase overall survival and life quality of cancer patient by enhancing the bioavailability of drug to the site of tumor by minimizing the exposure to normal cells and alleviating systemic side effects. Because of its favorable safety profile and clinical benefits, United States Food and Drug Administration (U.S. FDA) has approved polymer based in situ systems for prolonged locoregional activity. This article discusses the rationale for developing in situ systems for targeted delivery of anti-cancer agents with special emphasis on types of polymers used to formulate the in situ system. In situ formulations for locoregional anti-cancer drug delivery that are marketed and are under clinical trials have also been discussed in detail in this article.
Keywords: Locoregional